Calderon's Complex Interpolation of Morrey Spaces - Denny Hakim (IndoMS, 2020)
In this note we will discuss some results related to complex interpolation of Morreyspaces. We first recall the Riesz-Thorin interpolation theorem in Section 1.After that, we discuss a partial generalization of this theorem in Morrey spaces proved in St.We also discuss non-interpolation property of Morrey spaces given in BRV99, RV.In Section 3, we recall the definition of Calderón's complex interpolation method andthe description of complex interpolation of Lebesgue spaces.In Section 4, we discuss the description of complex interpolation of Morrey spaces given inCPP98, HS2, Lemarie, LYY. Finally, we discuss the description of complex interpolationof subspaces of Morrey spaces in the last section.This note is a summary of the current research about interpolation of Morrey spaces,generalized Morrey spaces, and their subspaces inCPP98, HS, HS2, H, H4, Lemarie, LYY.